Improving Arabic Learning Outcomes through the Implementation of the Small Group Discussion Strategy - Alfy Mamduh Nuruddin; Riza Nurlaila; Nurhalimah S.; Luthfi Muhyiddin; Aufa Alfian Musthofa (Journal of Arabic Language Teaching, 2026)
Arabic language learning in Indonesian secondary schools continues to face challenges, particularly low student engagement and limited communicative competence. Although collaborative learning strategies such as Small Group Discussion (SGD) have been widely discussed, empirical research on their application at the Madrasah Tsanawiyah (MTs) level within a Classroom Action Research (CAR) context remains limited. This study addresses this research gap by examining the effectiveness of SGD in improving Arabic learning outcomes and student activeness among Grade 7A students at Madrasah Tsanawiyah Negeri 3 Ngawi. The study employed a Classroom Action Research design based on the Kemmis and McTaggart model, conducted in two cycles involving planning, action, observation, and reflection. Data were collected through observation sheets, achievement tests, and student questionnaires. Data were analyzed using descriptive quantitative techniques, including mean scores and percentage improvements, supported by qualitative analysis of classroom observations and reflective notes. The results show substantial improvement in both achievement and engagement. The average score increased from 76.3 in Cycle I to 93 in Cycle II, while student enthusiasm rose from 70.1% to 92%. These findings confirm that SGD effectively promotes interactive, student-centered Arabic learning and enhances both academic performance and classroom participation. Pembelajaran bahasa Arab di sekolah menengah Indonesia terus menghadapi berbagai tantangan, terutama rendahnya tingkat keterlibatan siswa dan keterbatasan kompetensi komunikatif. Meskipun strategi pembelajaran kolaboratif seperti Diskusi Kelompok Kecil (DKK) telah banyak dibahas, penelitian empiris mengenai penerapannya di tingkat Madrasah Tsanawiyah (MTs) dalam konteks Penelitian Tindakan Kelas (PTK) masih terbatas. Penelitian ini menjawab kesenjangan penelitian tersebut dengan mengkaji efektivitas strategi SGD dalam meningkatkan hasil belajar bahasa Arab dan keaktifan siswa di kelas 7A Madrasah Tsanawiyah Negeri 3 Ngawi. Penelitian ini menggunakan desain Penelitian Tindakan Kelas berdasarkan model Kemmis dan McTaggart, yang dilaksanakan dalam dua siklus yang meliputi perencanaan, tindakan, pengamatan, dan refleksi. Data dikumpulkan melalui lembar observasi, tes prestasi, dan kuesioner siswa. Data dianalisis menggunakan teknik kuantitatif deskriptif, termasuk skor rata-rata dan peningkatan persentase, didukung oleh analisis kualitatif dari observasi kelas dan catatan refleksi. Hasil penelitian menunjukkan peningkatan yang signifikan baik dalam prestasi maupun keterlibatan. Skor rata-rata meningkat dari 76,3 pada Siklus I menjadi 93 pada Siklus II, sementara antusiasme siswa naik dari 70,1% menjadi 92%. Temuan ini menegaskan bahwa SGD secara efektif mendorong pembelajaran bahasa Arab yang interaktif dan berpusat pada siswa serta meningkatkan baik prestasi akademik maupun partisipasi di kelas.